A RUPTURE IN PHOTOJOURNALISM PRACTICES? A QUALITATIVE ANALYSIS OF AI-GENERATED IMAGERY WITHIN NEWS MEDIA PROFESSIONALS - Spaggiari, Chiara; Gemini, Laura (AoIR Selected Papers of Internet Research, 2026)
This study explores the legitimacy of AI-generated images in photojournalism and their potential role in documentary practices. While much of the discourse surrounding AI-generated images focuses on their involvement in disinformation and misinformation, less attention has been given to their possible documentary and informational applications. This research investigates how news media professionals assess the use of AI-generated images for documenting events and the ethical and procedural challenges they pose. Through a qualitative study involving 15 semi-structured interviews with photo-editors, photojournalists and documentary photographers in Italy, the study examines their perspectives on AI-generated images in news media contexts. Findings suggest that AI-generated images could be perceived not as a radical disruption but rather as a continuation of pre-existing illustrative trends. While AI-generated images may find a place in journalism, they should not be considered an extension of traditional photography but rather a distinct visual medium requiring its own ethical framework and editorial verification processes.